Right ventricular myxoma: A case report - Obrenović-Kirćanski Biljana; Mikić Aleksandar; Velinović Miloš; Božić Vesna; Kovačević-Kostić Nataša; Karan Radmila; Parapid Biljana; Đukić Petar; Savić Dragutin; Vraneš Mile (Vojnosanitetski Pregled)
Introduction. Myxomas arising from the right ventricle are extremely rare. Case report. We presented a 71-year-old patient with worsening symptoms of the exertional dyspnea and atypical chest pains lasting 6 months. A transthoracic and transesophageal echocardiogram revealed a large, 2.6 x 2.2 cm, ovoid, well-circumscribed, echogenic mass in the right ventricle outflow tract attached by small pedicle, partly obstructing the right ventricular outflow tract and protruding through the pulmonic valve during systole. The tumor was completely removed with the stalk and 5 mm of the surrounding tissue. The histopathological findings confirmed the diagnosis of myxoma. Conclusion. This case illustrates the usefulness of echocardiography both in diagnosis of patients with atypical symptoms without family history and associated syndromes (like Carney’s complex), and in surgical approach planning. It also stresses the importance of surgical excision of tumor as soon as possible following the diagnosis to prevent the complications such are: valvular obstruction, pulmonary embolization and syncopes.